Barriers influencing nurses' attitudes towards palliative care in the neonatal intensive care unit: a scoping review - Fatima Pacheco Sousa; Maria Alice dos Santos Curado (Nursing Research, Innovation and Development Centre of Lisbon (CIDNUR) of the Nursing School of Lisbon (ESEL), 2023)
Objectives: To identify the barriers that influence nurses' attitudes towards palliative care in the neonatal intensive care unit. Background: Neonatal nurses play a crucial role in caring for the newborn suffering from a complex chronic illness or who is at the end of life and needs palliative care. In the neonatal intensive care unit, the implementation of palliative care is inconsistent due to the existence of barrier  that influence nurses' attitudes when faced with the need to make decisions related to newborns' end-of-life or the suspension of curative treatments. Methods: Following the methodology designated by the Joanna Briggs Institute and the PRISMA-ScR as a complementary checklist, this scoping review was conducted in three phases and 10 databases were searched for relevant primary research studies, systematic reviews and meta-analyses, in English, Portuguese, French, and Spanish from 2016 to 2021. The data obtained through the extraction process were gathered in a table, and included the study characteristics, the population involved, the key findings related to the barriers influencing the nurses' attitudes towards the provision of palliative care in the neonatal unit and the instruments used to assess those attitudes. Results: Sixteen studies met the inclusion criteria. The main barriers identified by the studies are related to the absence of training in palliative care, difficulty in communication with parents and between health professionals, and the absence of policies related to the provision of neonatal palliative care. The semi-structured interview has been the most common and widely used instrument for qualitative studies. Questionnaires were selected for quantitative studies, with the NiPCAS being the most commonly used in the NICU. Conclusion: The barriers influencing nurses' attitudes towards the implementation of neonatal palliative care are identified by the scientific literature, however care remains inconsistent. The definition of training strategies and organizational policies can reduce the impact of barriers faced by neonatal nurses in the provision of palliative care.